Rol del profesional de enfermería en el acompañamiento emocional y educativo de la mujer con hemorragia posparto, a la luz de la teoría de los cuidados de Kristen Swanson (2021)
Postpartum hemorrhage is a complication and one of the causes of extreme maternal morbidity and mortality. The objective of the study was to examine the role of the nursing professional in the emotional and educational accompaniment of women with postpartum hemorrhage, both in the regulations in force in Colombia and in the evidence found in the world literature, in light of the theory that Kristen Swanson cared for. The present study corresponds to a documentary type literature review, where sixteen were recovered that met the inclusion criteria described in the methodology. As results, the categories that were based on the process of Kristen Swanson's theory are presented: first category: knowing the patient and the management of PPH, second category: being emotionally present, third category: doing what the woman needs, fourth category : enable to overcome the experience, fifth category: trust the capabilities of the patient. In conclusion, it is necessary for the nursing professional to transcend beyond medical and technical interventions and procedures, to approach the woman and her family from the emotional and educational component, which improves the nurse-patient relationship, favoring recovery.